Hubungan Antara Aktivitas Fisik Dengan Indeks Massa Tubuh Pada Situasi Pandemi Covid-19 - Magdalena, Riana; Budi, Didik Rilastiyo; Widanita, Neva; Syafei, Muhamad; Listiandi, Arfin Deri (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2021)
The Covid-19 pandemic has made changes in the routines of physical activity and sports carried out by students, so it is necessary to know the condition of the Body Mass Index (BMI) owned by students, especially sports students. The purpose of this study was to determine the relationship between physical activity and the condition of Body Mass Index in sports students. The research method uses a Corelational study with the side technique used, namely Total Sampling. The sample in this study were students of the Department of Physical Education, Jenderal Soedirman University with a total of 41 people consisting of 31 men and 10 women. The research instrument used a 24-hour Physical Activity Recall test to measure the level of physical activity and a Body Mass Index (BMI) test. Data analysis used the prerequisite test for normality and linearity, while the hypothesis test used the Chi-square test to determine whether or not there was a relationship between two variables. The results of data analysis showed that the level of physical activity carried out by students in the Covid-19 pandemic situation was in the less/low category and Body Mass Index (BMI) in the overweight or obese category. The conclusion of this study is that there is a relationship between the level of physical activity and Body Mass Index, meaning that the better the physical activity, the better the condition of the Body Mass Index. or normal.